Peran Imunitas Mukosa terhadap Infeksi Mycobacterium Tuberculosis: [The Role of Mucosal Immunity in Mycobacterium tuberculosis Infection] - Irmi Syafa’ah; Resti Yudhawati (Jurnal Respirasi, 2016)
Tuberculosis (TB) is one of major health problems in the world, with high morbidity and mortality rates. According to Global Tuberculosis Report 2015, Indonesia ranks as country with the 2nd highest number of TB cases in the world. Airway was described as a ‘gateway’ to the main pathogens, allergens and particles from the external environment. It has surveillance function that filtering beneficial and non-beneficial antigens, including Mycobacterium tuberculosis (MTB) as the causative agent of TB. MTB is a mucosal transmitted pathogen, infects human through mucosal tissue of respiratory tract. Airway mucosa was considered as the first barrier as well as inductive sites to initiate mucosal immune response against MTB. In this literature, the role of mucosal immune system, in this case especially airway mucosa, and its role against Mycobacterium tuberculosis infection in humans will be further discussed.